High construal level can help negotiators to reach integrative agreements: The role of information exchange and judgement accuracy. (25th September 2015) - Wening, Stefanie; Keith, Nina; Abele, Andrea E.
Abstract : In negotiations, a focus on interests ( why negotiators want something) is key to integrative agreements. Yet, many negotiators spontaneously focus on positions ( what they want), with suboptimal outcomes. Our research applies construal‐level theory to negotiations and proposes that a high construal level instigates a focus on interests during negotiations which, in turn, positively affects outcomes. In particular, we tested the notion that the effect of construal level on outcomes was mediated by information exchange and judgement accuracy. Finally, we expected the mere mode of presentation of task material to affect construal levels and manipulated construal levels using concrete versus abstract negotiation tasks. In two experiments, participants negotiated in dyads in either a high‐ or low‐construal‐level condition. In Study 1, high‐construal‐level dyads outperformed dyads in the low‐construal‐level condition; this main effect was mediated by information exchange. Study 2 replicated both the main and mediation effects using judgement accuracy as mediator and additionally yielded a positive effect of a high construal level on a second, more complex negotiation task. These results not only provide empirical evidence for the theoretically proposed link between construal levels and negotiation outcomes but also shed light on the processes underlying this effect.